2020
DOI: 10.1111/ijcp.13834
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F , CALR and MPL515L/K mutations and plateletcrit in essential thrombocythemia: A single centre's experience

Abstract: Aims JAK2V617F (JAK2), calreticulin (CALR) and MPL515L/K (MPL) mutations are important in essential thrombocythemia (ET) and may be associated with various clinical consequences of the disease. This study aimed to compare the clinical and haematological parameters of ET patients regarding the mentioned mutations and the role of plateletcrit (PCT). Methods Seventy patients who were diagnosed with ET between 2005 and 2017 in a single centre were included in this descriptive study. The initial symptoms and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The majority of our patients (77.8%) were treated with cytoreductive agents. In our study, the overall cytoreduction rate was comparable to that of a Romanian cohort (77.8% vs. 76.8%, respectively), although approximately half of the Romanian patients received cytoreductive therapy without ASA/antiplatelets or anticoagulants [ 23 ]. HU was the most preferred cytoreductive treatment in both patient cohorts.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The majority of our patients (77.8%) were treated with cytoreductive agents. In our study, the overall cytoreduction rate was comparable to that of a Romanian cohort (77.8% vs. 76.8%, respectively), although approximately half of the Romanian patients received cytoreductive therapy without ASA/antiplatelets or anticoagulants [ 23 ]. HU was the most preferred cytoreductive treatment in both patient cohorts.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, patients with CALR mutations in Tunisian and Belgian cohorts had higher platelet counts and lower hemoglobin levels and leukocyte counts than patients with JAK2 V617F mutations [ 18 , 22 ]. Ceylan et al [ 23 ] showed that patients with CALR mutations presented with higher platelet counts and lactate dehydrogenase levels compared to JAK2 - and MPL -mutated patients. Similarly, in our patient cohort, CALR -mutated patients had significantly higher platelet counts and lower hemoglobin levels (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations leading to platelet proliferation in ET have been identified in prospective studies. JAK2V617F mutations are found in 50 to 65% of the patients, CALR exon 9 mutations in 20 to 25%, and MPL exon 10 mutations in 5% (13). Another prospective study done on 40 patients with ET found the most frequent sequence variants were in the TET2 gene, followed by the KIT gene (14).…”
Section: Discussionmentioning
confidence: 99%